Flexible recruitment of semantic richness: context modulates body-object interaction effects in lexical-semantic processing - Tousignant, Cody; Pexman, Penny M. (Frontiers in Human Neuroscience, 2012)
Body-object interaction (BOI) is a semantic richness variable that measures the perceived ease with which the human body can physically interact with a word’s referent. Lexical and semantic processing is facilitated when words are associated with relatively more bodily experience (high BOI words, e.g., belt). To date, BOI effects have been examined in only one semantic decision context (is it imageable?). It has been argued that semantic processing is dynamic and can be modulated by context. We examined these influences by testing how task knowledge modulated BOI effects. We presented the same stimuli (high- and low-BOI entity words and a set of action words) in each of four action/entity semantic categorization tasks (SCTs). Task framing was manipulated: participants were told about one (actions or entities) or both (actions and entities) categories of words in the decision task. Facilitatory BOI effects were observed when participants knew that ‘entity’ was part of the decision category, regardless of whether the high- and low-BOI entity words appeared on the affirmative or negative side of the decision. That BOI information was only useful when participants had expectations that object words would be presented suggests a strong role for the decision context in lexical-semantic processing, and supports a dynamic view of conceptual knowledge.